Eksplorasi Perbedaan Kualitas Pelayanan antara Hotel Chain dan Hotel Lokal Independen di Kabupaten Magelang - Koesprayogo, Dwipayana; Maria Th, Aletta Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to explore the differences in service quality between chain hotels and independent local hotels in Magelang Regency, a tourism destination with unique characteristics due to its diverse visitors and strong local culture. The research employs a descriptive–comparative qualitative approach with four key informants selected through purposive sampling, consisting of operational managers/General Managers and front office supervisors from each hotel type. Data were collected through in-depth interviews, non-participatory observations, and document analysis, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The findings indicate that chain hotels excel in standardized service structures, consistent implementation of Standard Operating Procedures (SOP), evenly distributed staff professionalism, and integrated technological support such as PMS and CRM systems. In contrast, independent hotels demonstrate strengths in service flexibility, emotional closeness with guests, the incorporation of local wisdom, and higher levels of personalized service, although they face challenges in maintaining consistency. The differences in service quality are influenced not only by hotel type but also by organizational factors, work culture, staff competence, technology, and guest characteristics. This study concludes that both hotel types offer complementary service approaches; optimal service quality is achieved when strong operational standards are combined with personalized touches that adapt to guest needs. These findings provide theoretical contributions to the study of hospitality service quality and practical recommendations for hotel management to enhance service competitiveness in tourism destinations.